SHUKUR XOLMIRZAYEV HIKOYALARIDA DIALEKTIZMLAR - Abduvaliyeva, Dilnoza (FILOLOGIYA UFQLARI JURNALI, 2022)
This article talks about language features of some stories of Uzbekistan public poet Shukur Kholmirzayev. In the works of the of the poet we can mostly the evaluation of the case where the text dialectal words are used and their means are interpreted.